KEANEKARAGAMAN DAN KELIMPAHAN JENIS BURUNG DI DESA PENYANGGA TAMAN NASIONAL BERBAK DAN SEMBILANG (STUDI KASUS DI DESA SIMPANG KECAMATAN BERBAK KABUPATEN TANJUNG JABUNG TIMUR - Khoirunnisa; Iswandaru, Dian; Wulandari, Christine; Herwanti, Susni; Novriyanti; Mora, Andita Minda; Taufiq, Azizul Rahmad (Jurnal Nusa Sylva, 2025)
Berbak and Sembilang National Parks are conservation areas that become habitats for various types of plants and animals, including birds. This stud ypurpose to find species diversity, species evenness, species richness, dominance, species abundance and bird conservation status in Simpang Village. Data collection was carried out using the point count method and transect as many as 3 points which were assumed to represent one ecosystem, namely swamp ecosystems, shrubs and water bodies. The results obtained were 36 types of birds from 22 families. The value of the diversity index in the type of swamp ecosystem of 2,295 and the water body of 2,940 is in the medium category and the shrub ecosystem of 3,754 is relatively high. The three types of ecosystems have a stable distribution of types ranging from 0.21 < E < 1, no species dominate, but have a varied wealth of species, namely in low swamp ecosystems, medium shrub ecosystems and high water body ecosystems. This is due to the existence of three different types of ecosystems in the village, so that each ecosystem has a diverse species composition. Thus, Simpang Village is still classified as having a well-maintained diversity of birds, but still has to make efforts to conserve birds so that the bird population does not decrease, one of which is through continuous counseling by involving parties to educate and increase public awareness in the conservation of birds and their habitats.